The use, integration and value of performance analysis to GAA coaches - Martin, D.; Swanton, A.; McGrath, D.; Bradley, J. (Journal of Human Sport & Exercise, 2017)
Performance analysis (PA) has become integral to the multi-million euro preparation of intercounty GAA teams (GAA, 2013). With little research on the coaching practice of GAA coaches, this paper explores their engagement with PA. Its aims were to examine the use, integration and value of PA to coaches. A sample of 12,500 (minimum level 1 Coaching Ireland qualified) coaches were selected to complete an online-survey with 538 respondents across 37 sports. As the highest responding cohort (n=144), data for the GAA coaches was isolated for further analysis. PA was used by 49% of GAA coaches. These coaches were more likely to have 10+ years coaching experience (Xi2 = 20.7 p = 0); be qualified beyond GAA Award 1 (Xi2 = 14.0 p = 0) and coach at intercounty level (Xi2 = 12.3 p = 0). Coaches using PA had access primarily to match statistics (81%); only 49% had access to match video. The most popular tools for data collection were hand notation (65%), Dartfish (38%) and Apps (38%). Coaches cited resources and knowledge as key barriers to progressing their use of PA. Reliability of information was not identified as an issue. 88% of coaches using PA felt it was important / essential to their practice. The findings indicate that GAA coaches have substantially more access to quantitative information compared to video feedback. This lack of video to contextualise and validate data has potential to hamper the interpretation of information by a coach thus impacting their subsequent interventions. In GAA coach education, more emphasis could be placed on the importance of contextualising statistics with video and the potential of video feedback to players. Coaches should be encouraged to question the reliability of match statistics and equipped with appropriate strategies to minimise errors in data collection.